Effect of Supplementation Level of Black Kabesak (Acacia nilotica) Fruit on The Intake and Digestibility of Dry Matter and Organic Matter in Cull Onggole Cows Fed a Basal Diet Containing Banana stems, Rice bran and Rice Straw - I Gusti Ngurah Jelantik; Robertus A. Dahis; Imanuel Benu (Animal Husbandry Study Program, Faculty of Agriculture, Timor University, 2022)
This study aimed to determine the effect of the level of supplementation of black kabesak fruit (Acacia nilotica) on the intake and digestibility of dry matter (DM) and organic matter (OM) in Ongole cows maintained on a basal diet containing banana stems, rice bran and rice straw. This study used 3 cull Onggole cows (BW range 194-210.5 kg) aged 8-9 years. The experiment was conducted following the Latin Square Design (LSD) with 3 treatments and 3 periods as replication. The treatments were basal feed and supplemented with Acacia nilotica fruit at a level of 0% (BAN0), 0.5% (BAN0.5), 1% (BAN1) of the animal's body weight respectively. The results showed that supplementation of Acacia nilotica fruit up to 1% of body weight increased (P<0.01) the intake of DM and OM. Meanwhile, the supplementation of A. nilotica at 1% BW increased the digestibility of DM but had no effect on the digestibility of OM. The conclusion of the study was that the supplementation of black kabesak fruit (Acacia nilotica) up to a level of 1% BB could be beneficial in increasing the intake of DM and OM and the digestibility of DM in cull Onggole cows.